TIME DELAY BETWEEN IMAGES OF THE LENSED QUASAR UM673 - Koptelova, E.; Chen, W. P.; Chiueh, T.; Artamonov, B. P.; Oknyanskij, V. L.; Nuritdinov, S. N.; Burkhonov, O.; Akhunov, T.; Bruevich, V. V.; Ezhkova, O. V.; Gusev, A. S.; Sergeyev, A. V.; et al. (Одеські астрономічні публікації, 2012)
We study brightness variations in the double lensed quasar UM673 (Q0142-100) with the aim of measuring the time delay between its two images. Methods.. We analyzed the V, R and I-band light curves of the A and B images of UM673, which cover ten observational seasons from August 2001 to November 2010. We also analyzed the time evolution of the difference in magnitudes (flux ratio) between images A and B of UM673 over more than ten years. We find that the quasar exhibits both short-term (with an amplitude of ~ 0.1 mag in the R band) and long-term (with an amplitude of ~ 0.3 mag) variability on timescales of about several months and several years, respectively. These brightness variations are used to constrain the time delay between the images of UM673. From a cross-correlation analysis of the A and B quasar light curves and an error analysis we measure a mean time delay of 89 days with an rms error of 11 days.